Draft Annual Plan 1981-82 Vol. II-Sectoral Reviews Uttar Pradesh - Planning Commission (Planning Commission, 1980)
The economy of Uttar Pradesh is predominantly agricultural and will continue to be so in the foreseeable future. Future prospects in relation to the development of crop husbandry in the State continue to be bright. The available infrastructural support has been able to take the total production of foodgrains in the State to 231 lakh tonnes in the year 1978-79. With this background, it is quite evident that the Slate should strive towards a higher rate of growth of production from field crops than has been achieved so far.
Uttar Pradesh Planning Department